Stress-resistant but phage-sensitive host mutants induced by phage T4 ghost adsorption - Kenzaka, Takehiko; Tani, Katsuji (Frontiers in Microbiology, 2025)
The main effect of lytic phages on the host is cell lysis, and genetic impact of short-term contact between the host and the phage remains unknown unless genetic exchange occurs. In this study, we found that the adsorption of a lytic phage to the host cell can rapidly alter the genetic and physiological properties of hosts that have escaped lysis without relying on gene transfer. After adsorption of the lytic phage T4 to Escherichia coli (host) cells, 1% of E. coli cells exhibited an approximately 85-fold increase in spontaneous mutant frequency, which was measured based on antibiotic resistance. Phage ghosts increased the incidence of mutator strains exhibiting elevated expression of the error-prone DNA polymerase IV gene (dinB), while the emergence of mutators was suppressed in the dinB-deficient strain. Adsorption of ghosts onto the cell surface triggered global changes in gene expression in surviving cells, including upregulation of DNA polymerase IV. This upregulation led to mutations in host genes such as tfaR and marR, which were associated with high mutant frequency. Phage- or ghost-derived mutator strains showed a higher frequency of resistance to reactive oxygen species and acid stresses than the parental strain but a lower frequency of resistance to phage T4. These findings suggested that phage ghosts may promote host cell survival and alter their physiological characteristics, thus contributing to the production of progeny virions in future phage attacks.